Hydrocarbons as alternative refrigerants in domestic refrigerators - S, Parashurama; Saleel, C. Ahmed; M. S., Govindegowda; Khan, Sher Afghan (Blue Eyes Intelligence Engineering & Sciences, 2019)
The thermodynamic and volumetric properties of hydrocarbons namely Propane, Cyclopropane, Propene, Methyl acetylene, Propadiene and Dimethyl ether as replacements to substitute R134a have been assessed by means of SRK equation of state. The pressure magnitude, enthalpy, entropy, and specific capacity at the vapor and fluid phase have been analyzed over the temperature range from -250C to +55 0C. Ten state point vapor compression cycle is used to carry out the thermodynamic investigation of 89W local refrigerator. The theoretical enactment of the hydrocarbons has been comparatively assessed using standard refrigeration parameters such as displacement volume, volumetric efficiency, starting torque, refrigerating effect, discharge temperature, COP and rating of the motor. According to our results, Propane and Propene are appropriate and recommended as alternatives of R134a with lower displacement compressor and Cyclopropane as a direct substitute. Also implications with respect to material and lubricant oil compatibility, heat transfer characteristics are discussed.